Semi-Auto Lemongrass Harvesting Machine - Hafizi, Nur Syahirunnisaa Afini; Mohd Rashidi, Muhammad Muhaimin Ajmal; Amizy, Mohammad Aiman; Othman, Muhammad Azri; Ab Rahman, Rosdi; Basri, Azizul Qayyum (Multidisciplinary Applied Research and Innovation, 2025)
Lemongrass harvesting remains labor-intensive, time-consuming and of inconsistent quality when performed manually, limiting scalability to meet increasing demand. This study introduces a semi-automatic lemongrass harvesting machine designed to reduce labor dependency and increase efficiency. Developed using a structured engineering process, the prototype integrates a two-stroke engine, a chain sprocket assembly and a rake blade for continuous uprooting. Small-scale laboratory tests and limited field testing were conducted due to financial constraints. Results showed that the machine required 10 seconds per harvesting cycle compared to 12 seconds manually, achieving 360 clumps per hour (720 kg/h) compared to 300 clumps per hour (600 kg/h) using the manual method. This equates to a 20% efficiency increase and a time saving of approximately 7 hours per hectare. Although the improvement in performance is clear, large-scale field trials are recommended to confirm reliability under real-world conditions. Future improvements should focus on integrating security, remote monitoring, and adjustable blade mechanisms to optimize practicality and usability.